Genomic Elements in Health, Disease and Evolution Junk DNA - Felekkis, Kyriacos; Voskarides, Konstantinos (Springer New York : Imprint: Springer, 2015)
This book provides a thorough review of various non-coding genomic elements and discusses in depth their role in health, disease and evolution. It begins with an exploration of non-coding RNA molecules miRNAs, piRNAs, LncRNAs and transposable elements as these moieties dominate the scientific literature the last ten years. The second part of the book discusses copy number variation regions, mini and micro satellites, and proximal and distal elements of the genome. The last section of the book focuses on the review of well-known non-coding regions of the genome, introns, centromeres and telomeres, but enriched with newly discovered functions. As the vast amount of data in regards to these elements is attributed to a great degree to the growing technology in the field of biomedicine, the last chapter of the book discusses the latest development in the field of Next Generation Sequence and the potential applications of this technology in the study of non-coding regions of the genome. This new volume provides an in depth background on 'junk DNA' and helps set the stage for future research, and is an essential tool for those in the field.